Loggerhead (Caretta caretta) and Leatherback (Dermochelys coriacea) nesting activity along the Maputaland coast (South Africa) : 1965 - 2002 - Wright, Ruth Vivienne (Department of Oceanography, 2014)
Includes bibliographical references (leaves 59-63).